Efficient degradation of organic dyes and reduced Cr(VI) in environmental water purification by in-situ deposition of silver nanoparticles on polydopamine-modified M-ATP/PCN - Zhe Zhang; Nan Zhang; Yani Liu; Qiqi Fang; Jiao Xi; Yuxuan Xiao; Pengxin Zhou; Lei Xu (Catalysis Communications, 2022)
This paper presents the synthesis of Ag@PDA/M-ATP/PCN photocatalysts for the removal of heavy metals and organic dyes via the in-situ reduction method. According to the photoluminescence (PL) spectra, time-resolved fluorescence spectra, UV–vis absorption spectra, transient photocurrent response spectra, and the EIS results, the composite of M-ATP, PDA coating, and single-atom Ag doping further promotes the separation of the photogenerated carriers, reduces the band-gap, improves the photocatalytic performance, and promotes the synergistic effect of charge separation and transfer to enhance the photocatalytic performance. The catalysts prepared by this composite strategy exhibit high charge separation efficiency, higher catalytic efficiency, and better stability than the conventional single-method modified polymeric carbon nitride catalysts.